Reconsideration of Membership Dues: New International Fee Structure Adopted. - Sonnenwald, Diane H. (Bulletin of the Association for Information Science & Technology)
EDITOR'S SUMMARY To increase international membership, Special Interest Group/International Information Issues (SIG/III) successfully proposed in 2012 to lower membership fees for ASIS&T members working in developing nations. The ASIS&T Board later lowered fees for students and early and transitional professionals from these countries. Though these moves boosted member numbers, other disparities became evident, including fees that remain prohibitive for institutions in developing nations and even for many potential individual and institutional members in countries rated 'high' or 'very high' in the United Nations Human Development Index. The Board approved the International Relations Committee's proposal to base membership rates on countries' gross national income (GNI) per capita, sorting countries into three tiers. Membership fees for countries in the middle tier would be 30% of the usual fee and 20% for the lower tier and exclude print publications, the fee strategy used by the Association for Computing Machinery (ACM).